A generic network function virtualization manager and orchestrator for content-centric networks. - Castillo Lema, José (2019)
Network Functions Virtualization (NFV) offers an alternative way to design, deploy, and manage networking functions and services by leveraging virtualization technologies to consolidate network functions into general-purpose hardware platforms. On the past years extensive effort has been made to evolve and mature NFV technologies over IP networks. However, little or no attempts at all have been made to incorporate NFV into Information-Centric Networks (ICN). This work explores the use and implementation of Virtual Network Functions (VNFS) in Content-Centric Networks (CCN) and proposes the use of the Named Function Networking (NFN) paradigm as means to implement network functions and services in this kind of networks, distributing the network functions and services through the networks nodes and providing flexibility to dynamically place functions in the network as required and without the need of a central controller. The Dynamic Named Function Architecture (DNFA) was proposed, a scalable and flexible framework that allows the automated deployment, management, monitoring, optimization and lifecycle management of named functions over CCN infrastructures, following the European Telecommunications Standards Institute (ETSI) NFV architectural guidelines and using an extended customized OASIS TOSCA NFV profile template for VNF meta-data definition. Evaluation of the framework was carried out on a private OpenStack testbed scenario through a DPI VNF implementation.